Comparison of DDOS detection methods in real world scenario - Bidikov, Vladislav; Mishkovski, Igor (Ss Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2023)
In this paper we will see the current and new developed methods for distributed denial of service attack (DDOS) detection. We will also see some of the possibility for mitigation of attacks in scenarios where they are detected sooner. We will use data from the DDOS attack in June/August/September 2022 on the Faculty and learn valuable lessons from there.
Keywords: DDOS attacks, networks, protection, netflow, sflow, bgp